A summary of bibliometric analysis on the publication trends in technology roadmapping - Ahmad Zaidi, Mohamad Faizal; Belal, H.M. (School of Technology Management and Logistics, 2019)
Technology roadmapping is “a technique to capture diverse information in technology evolution and new product development” (Petrick & Echols, 2004, p.89). It is part of technology planning that deal with increasing competitive environment (Garcia & Bray, 1997). Technology roadmapping is crucial for creating alignment between technology and organizational goals (Phaal, Farrukh, & Probert, 2005). One of the applications is to support strategic planning in relations to technology, product, and market (Phaal, Farrukh, & Probert, 2004). It can also be applied for service planning, capability planning, longrange planning, knowledge asset planning, program planning, process planning, and integration planning (Phaal, Farrukh, & Probert, 2001). The initial works on technology roadmapping was appeared for the first time in the late 70’s (Phaal, Farrukh, & Probert, 2005). With over two decades of literatures, the ground works of technology roadmapping have been well established. As a result, this study will summarize the publication trends in technology roadmapping based on the bibliometric analysis of references.